2007
DOI: 10.1002/jrs.1816
|View full text |Cite
|
Sign up to set email alerts
|

A Raman spectroscopic study of the Mapungubwe oblates: glass trade beads excavated at an Iron Age archaeological site in South Africa

Abstract: Oblate seed beads (2-4 mm) excavated on Mapungubwe hill, an Iron Age site in South Africa, were analysed with Raman microscopy and supportive techniques to determine the glass technology and pigments used to produce the beads. The Raman spectra and XRF analysis of the beads classify the glass as a typical soda/lime/potash glass similar to Islamic glass from the 8th century (Ommayad), but with higher levels of aluminium, iron and magnesium. The turquoise, bright green, bright yellow and orange colours were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
112
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(125 citation statements)
references
References 32 publications
13
112
0
Order By: Relevance
“…For Mapungubwe, occupation on the Hill and Mapungubwe Southern Terrace seem to relapse in the fourteenth century. This also supports the conclusion made by Prinsloo and Colomban (2008) on the Fig. 8 The modelled dates for selected elite sites in southern Africa basis of a Raman spectrometric study of Chinese porcelain from the hill.…”
Section: Bayesian Modelling Of Zimbabwe Culture Radiocarbon Datessupporting
confidence: 85%
See 1 more Smart Citation
“…For Mapungubwe, occupation on the Hill and Mapungubwe Southern Terrace seem to relapse in the fourteenth century. This also supports the conclusion made by Prinsloo and Colomban (2008) on the Fig. 8 The modelled dates for selected elite sites in southern Africa basis of a Raman spectrometric study of Chinese porcelain from the hill.…”
Section: Bayesian Modelling Of Zimbabwe Culture Radiocarbon Datessupporting
confidence: 85%
“…A Raman spectrometric study of the chemical composition of the celadon recovered from Mapungubwe Hill compared its chemistry with that recorded in Chinese factories. The recipes revealed that the porcelain was manufactured in China from the fourteenth century onwards (Prinsloo and Colomban 2008;Prinsloo et al 2011). This suggests that Mapungubwe may not have been abandoned by AD 1290 as currently believed.…”
Section: Discussion: Towards a New Framework For Zimbabwe Culture Arcmentioning
confidence: 95%
“…Recently we have developed a methodology combining visual classification based on morphology, X-ray fluorescence (XRF) and Raman spectroscopy to classify trade beads imported into southern Africa between the eighteenth and sixteenth centuries AD [6]. This methodology was based on our previous work on glass trade beads recovered from K2 and Mapungubwe Hill, the capital sites of southern Africa's first state complex in the Limpopo River Basin [20][21][22]. In studying the beads from Magoro Hill, we follow the same experimental procedures for classifying beads imported up to the seventeenth century AD and extend this approach to beads imported after the seventeenth century, making use of the database compiled for more recent beads retrieved from Mapungubwe Hill.…”
Section: Site History and Archaeological Contextmentioning
confidence: 99%
“…3) as they are made of soda glass. However, it has previously been shown that the resonance-enhanced Raman spectrum of the "Fe-S" chromophore, with a strong band at ~415 cm −1 superimposed on the SiO 4 bending vibrations around 500 cm −1 of the glass spectrum [20,22], causes the formation of a separate group (A) consisting of black beads with Raman spectra mostly independent of glass structure [20]. Although East-Coast Indo-Pacific beads can be opaque black and brownish-red or translucent yellow, soft orange, green and blue-green, only black EC-IP beads were identified based on morphology.…”
Section: Beads Classified As Indo-pacific Beads (Fig 5)mentioning
confidence: 99%
“…Koleini et al (2015) have proposed a new methodology for the classification of glass beads from southern Africa. This classification is the result of a number of experiential tests carried out on beads from a number of sites in the region, primarily the Shashe-Limpopo valley (Prinsloo et al 2008;2011;Tournie 2012) and north-eastern Botswana (Koleini et al 2015).…”
Section: Background To Glass Bead Studies In Southern Africamentioning
confidence: 99%